Implantação de centros de distribuição de produtos farmacêuticos na cidade de Uberlândia (MG) - Ramos, Paulo de Tarso Ricci (2015)
The objective of this study is to determine, based on urban freight logistics concepts, the optimal location, of a distribution center and the optimal routing for the distribution of pharmaceutical products, starting this CD, in the city of Uberlândia, MG, using the TransCAD software. The case study was conducted in a company\'s retail segment sales of pharmaceutical products nationwide, which have 12 branches established in the city. Due to the high costs of delivery, the risk of cargo theft related to the pharmaceuticals segment and the great competition between drugstores and even among other general retailers such as supermarkets and convenience stores, these companies have consistently sought alternatives to optimize operations storage and distribution. In the generation of scenarios, TransCAD software was used to obtain the optimal location of distribution centers and the optimal routing of the distribution of the products (s) center (s) distribution (s) for branch offices in the city, generating a reduction in costs of approximately 10% of the company\'s logistics costs in the city of Uberlândia, MG , representing values in the monthly amount of R $ 27,884.16 or R $ 334,609.92 annually.The concepts adopted relied on methodologies from Urban Freight Logistics and the importance of choosing a optimal place operationally for the installation of a distribution center, which handles high value added goods and strict control of health agencies such as ANVISA (National Health Surveillance Agency). For routing, were initially defined a current (2013) and a future scenario (2017) aimed to cover the growth prospect of the market.